Indigenous Sustainability and Post-Earthquake Vulnerabilities: A Case Study of the Traditional City Khokana - Shrestha, Anjana (Tribhuvan University Journal, 2026)
Traditional cities have quietly operationalized localized resource management and self-sufficiency for centuries. However, in the Nepalese context, traditional cities are generally studied through a heritage and conservation lens, though to a lesser extent through a sustainability lens. This study addresses this knowledge gap by examining the sustainability of Khokana, a traditional city also affected by rapid urbanization and post-Gorkha earthquake reconstruction. The objective of the study is to investigate a traditional city’s inherent capacity for self-sufficient resource management and its response to rapid urbanization and sudden disasters. The study applies the concept of sustainability across the six dimensions: land use, built forms, accessibility, open spaces, water management, and waste management, which are identified through a literature review. The study adopts a descriptive case study methodology and collects qualitative data through field observations, interviews, and a literature review of journals, articles, and governmental and institutional reports. Findings show that Khokana demonstrates sustainable characteristics through mixed land use, compact built form, pedestrian accessibility, multifunctional open spaces and efficient water and waste management. However, the study also identifies city congestion, vehicular intrusion, and wanton conversion of traditional built forms due to rapid urbanization and the post-Gorkha earthquake. The study concludes that while traditional cities like Khokana offer highly valuable lessons for modern sustainable cities, this city is currently at risk of losing its inherent sustainability characteristics. Immediate planning and policies are required to balance rapid urbanization and disaster resilience with sustainability characteristics.